2016
DOI: 10.1088/1748-9326/11/1/014013
|View full text |Cite
|
Sign up to set email alerts
|

Projected increases in the annual flood pulse of the Western Amazon

Abstract: The impact of a changing climate on the Amazon basin is a subject of intensive research because of its rich biodiversity and the significant role of rainforests in carbon cycling. Climate change has also a direct hydrological impact, and increasing efforts have focused on understanding the hydrological dynamics at continental and subregional scales, such as the Western Amazon. New projections from the Coupled Model Inter-comparison Project Phase 5 ensemble indicate consistent climatic warming and increasing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 43 publications
1
43
0
1
Order By: Relevance
“…; Zulkafli et al. ) and lower water levels and less precipitation during the dry season (Phillips et al. ; Espinoza et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Zulkafli et al. ) and lower water levels and less precipitation during the dry season (Phillips et al. ; Espinoza et al.…”
Section: Discussionmentioning
confidence: 99%
“…, ; Zulkafli et al. ). Duration of intensive floods included consecutive days when water level exceeded 117.65 m asl.…”
Section: Methodsmentioning
confidence: 99%
“…The large land surface models that use this reanalysis data have yielded information essential for understanding the complexity of tropical ecosystems. The Joint UK Land Environment Simulator, for example, has predicted that in the Amazon Basin, climate change will lead to increased seasonality of precipitation (Zulkafli et al, ), prolonged droughts (Boisier, Ciais, Ducharne, & Guimberteau, ), and larger floods. Recently, water isotope data have been collected remotely.…”
Section: Integrating Field‐ and Modelling‐based Methodsmentioning
confidence: 99%
“…While these projections of a roughly 10-30% decrease in precipitation by the end of the century appear to be quite robust, given that they have been reproduced by multiple studies employing different methodologies, the uncertainty regarding future precipitation changes is much larger in the more humid inner tropics. Buytaert et al (2010) and more recently Zulkafli et al (2016), for example, showed that in the Andes of Ecuador, models have difficulties in even agreeing on the sign of future changes in precipitation. Nevertheless, some studies suggest that the moisture flux from the Amazon basin to the Andes may weaken under a future warming-scenario (e.g.…”
Section: Climate Projectionsmentioning
confidence: 99%